2019
DOI: 10.1098/rspb.2019.0184
|View full text |Cite
|
Sign up to set email alerts
|

Silicified cell walls as a defensive trait in diatoms

Abstract: Diatoms contribute nearly half of the marine primary production. These microalgae differ from other phytoplankton groups in having a silicified cell wall, which is the strongest known biological material relative to its density. While it has been suggested that a siliceous wall may have evolved as a mechanical protection against grazing, empirical evidence of its defensive role is limited. Here, we experimentally demonstrate that grazing by adult copepods and nauplii on diatoms is approximately inversely propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 55 publications
3
64
0
Order By: Relevance
“…This experiment highlights that size diversity (Fig. 8b) is controlled not only by the rate of supply of the limiting nutrients, but also by size-specific grazing (Armstrong, 1994;Poulin and Franks, 2010;Ward et al, 2012).…”
Section: Size Class Diversitymentioning
confidence: 76%
See 1 more Smart Citation
“…This experiment highlights that size diversity (Fig. 8b) is controlled not only by the rate of supply of the limiting nutrients, but also by size-specific grazing (Armstrong, 1994;Poulin and Franks, 2010;Ward et al, 2012).…”
Section: Size Class Diversitymentioning
confidence: 76%
“…Obviously, nutrient supply rate (a bottom up process) cannot alone lead to high size diversity. Top-down processes are essential for the build-up of size classes with higher nutrient supply (see also Poulin and Franks, 2010). Considering only correlations with productivity would lead one to miss this important biotic interaction as a control on diversity.…”
Section: Discussionmentioning
confidence: 99%
“…There are also specific differences between functional groups in cell elemental stoichiometry, and palatability to grazers (diatoms and coccolithophores, with their hard surface covering deter grazers, see e.g. Monteiro et al, 2016, Pančić et al, 2019. The smallest phytoplankton have the highest affinity for nutrients (Edwards et al, 2012) as a result of the lowest surface to volume ratio in larger cells (Kiorboe 1993, Raven, 1994.…”
Section: Numerical Modelmentioning
confidence: 99%
“…The shell has the highest mechanical strength relative to its density of any known biological material (Aitken, Luo, Reynolds, Thaulow, & Greer, 2016) and the consequent force required to crush the cell wall is remarkable (Hamm et al., 2003; Wilken et al., 2011). Recent experiments have indeed demonstrated that the shell provides partial protection against copepod grazing (Liu, Chen, Zhu, & Harrison, 2016; Pančić, Torres, Almeda, & Kiørboe, 2019). Thus, a six‐fold increase in silica content in a variety of diatoms decreased the predation mortality due to a copepod grazer by four‐fold and entirely prevented small copepod nauplii from consuming the diatoms (Pančić et al., 2019).…”
Section: Introductionmentioning
confidence: 99%